Differences in skeletal microarchitecture and strength in African‐American and white women. (18th September 2013) - Putman, Melissa S; Yu, Elaine W; Lee, Hang; Neer, Robert M; Schindler, Elizabeth; Taylor, Alexander P; Cheston, Emily; Bouxsein, Mary L; Finkelstein, Joel S
ABSTRACT African‐American women have a lower risk of fracture than white women, and this difference is only partially explained by differences in dual‐energy X‐ray absorptiometry (DXA) areal bone mineral density (aBMD). Little is known about racial differences in skeletal microarchitecture and the consequences for bone strength. To evaluate potential factors underlying this racial difference in fracture rates, we used high‐resolution peripheral quantitative computed tomography (HR‐pQCT) to assess cortical and trabecular bone microarchitecture and estimate bone strength using micro–finite element analysis (µFEA) in African‐American (n = 100) and white (n = 173) women participating in the Study of Women's Health Across the Nation (SWAN). African‐American women had larger and denser bones than whites, with greater total area, aBMD, and total volumetric BMD (vBMD) at the radius and tibia metaphysis (p < 0.05 for all). African‐Americans had greater trabecular vBMD at the radius, but higher cortical vBMD at the tibia. Cortical microarchitecture tended to show the most pronounced racial differences, with higher cortical area, thickness, and volumes in African‐Americans at both skeletal sites (p < 0.05 for all), and lower cortical porosity in African‐Americans at the tibia (p < 0.05). African‐American women also had greater estimated bone stiffness and failure load at both the radius and tibia. Differences in skeletal microarchitecture and estimated stiffness and failure load persisted even after adjustment for DXA aBMD. The densitometric and microarchitectural predictors of failure load at the radius and tibia were the same in African‐American and white women. In conclusion, differences in bone microarchitecture and density contribute to greater estimated bone strength in African‐Americans and probably explain, at least in part, the lower fracture risk of African‐American women. © 2013 American Society for Bone and Mineral Research.